2014
DOI: 10.1002/nau.22645
|View full text |Cite
|
Sign up to set email alerts
|

Results of a randomized, double‐blind, parallel‐group, placebo‐ and active‐controlled, multicenter study of mirabegron, a β3‐adrenoceptor agonist, in patients with overactive bladder in Asia

Abstract: Mirabegron 50 mg once daily for 12 weeks was superior to placebo in reducing the frequency of micturitions in patients with symptoms of OAB in Taiwan, Korea, China, and India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 25 publications
3
80
1
2
Order By: Relevance
“…Mirabegron, which is a β3-adrenoceptor agonist, has effects on urgency, urinary incontinence and frequency , Kuo et al, 2014 in patients with the overactive bladder syndrome (OAB). Those studies did however not specifically analyze the effect of mirabegron in patients with BOO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mirabegron, which is a β3-adrenoceptor agonist, has effects on urgency, urinary incontinence and frequency , Kuo et al, 2014 in patients with the overactive bladder syndrome (OAB). Those studies did however not specifically analyze the effect of mirabegron in patients with BOO.…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin II receptors, on the other hand, are downregulated, and this is of possible relevance for urinary tract dysfunction in rats with 4 BOO (Yamada et al, 2009). Accordingly, current therapies for lower urinary tract symptoms target membrane receptors, including M3 muscarinic receptors (Andersson 2001) and β3-adrenergic receptors , Kuo et al, 2014. Our knowledge regarding effects of BOO on membrane receptor expression is still limited however, and an unbiased survey of receptor expression in BOO may disclose novel targets for therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these studies, mirabegron 50 mg/day was shown to be efficacious in patients with overactive bladder syndrome in large (n [ 1000) placebo-and active treatment-controlled trials conducted in Japan [16] and Taiwan, Korea, China and India [17].…”
Section: For Whom Is Mirabegron Indicated?mentioning
confidence: 98%
“…Mirabegron is the first β3 agonist to be used in clinical practice. [50][51][52][53] (D) To assess the efficacy and tolerability of this drug therapy in the treatment of idiopathic overactive bladder (IOAB), two phase II 54,55 (B) and six phase III [56][57][58][59][60][61] (A) randomized clinical trials (RCTs) recruited more than 10,500 adult patients. Of these, seven were randomized, double-blind and placebo-controlled with follow-up of four (one study) and 12 (six studies) weeks, and one was non-placebo-controlled (vs. tolterodine) with 12-month follow-up.…”
Section: Tolterodine Tartratementioning
confidence: 99%